Severe combined immunodeficiency (SCID) presenting with neonatal aplastic anemia. Issue 11 (22nd May 2015) - Scott, Angela; Glover, Jason; Skoda‐Smith, Suzanne; Torgerson, Troy R.; Xu, Min; Burroughs, Lauri M.; Woolfrey, Ann E.; Fleming, Mark D.; Shimamura, Akiko
<x xml:space="preserve">Abstract</x> Aplastic anemia in the neonate is rare. We report a case of severe combined immunodeficiency (SCID) presenting with neonatal aplastic anemia. This report highlights the importance of considering SCID early in the evaluation of neonatal aplastic anemia prior to the development of infectious complications. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.